PENGARUH KEPERCAYAAN DIRI DAN KETERAMPILAN KOMUNIKASI INTERPERSONAL TERHADAP NIAT BERWIRAUSAHA MAHASISWA FAKULTAS EKONOMIKA DAN BISNIS UNIVERSITAS NEGERI SURABAYA - Devina Reva Agustiyan; Novi Marlena (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
Educated unemployment remains a pressing issue in Indonesia, particularly among university graduates. The Faculty of Economics and Business at Surabaya State University (FEB UNESA) has sought to foster entrepreneurial intention through courses, training, and entrepreneurship programs. Nevertheless, students’ intention to pursue entrepreneurship has not yet reached an optimal level. This study aims to analyze the influence of self-confidence and interpersonal communication skills on entrepreneurial intention among FEB UNESA students. The research applied a quantitative survey method with 373 active students from the 2021–2023 cohorts selected via purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS 25. The findings reveal that self-confidence does not significantly affect entrepreneurial intention, while interpersonal communication skills have a positive and significant effect. These results emphasize the crucial role of soft skills, particularly interpersonal communication, in preparing students to become competitive young entrepreneurs.